Continuous beams on elastic supports an alternative equation - Pacheco, Edgardo S.
The integrated equation of the elastic curve of an elastically supported continuous beam that is acted on by any number of concentrated forces, concentrated couples, and uniformly varying loads is obtained by using the Laplace transformation. The support may consist of a Winkler foundation, and/or simple supports and/or cantilever supports which may be linearly elastic or rigid.